Socialization of Law Number 1 of 2023 on the Criminal Code: Readiness of Law Enforcement in Implementing Community Service as an Alternative to Imprisonment at SMK Muhammadiyah 02, Setu District, South Tangerang City - Martahan Siburian; Faisal Koerni; Helmi Budi Setiawan; Intan Puspita Sari; Feby Nur Safitri; Bambang Santoso (Yayasan Daarul Huda Kruengmane, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) marks a fundamental transformation in Indonesia’s penal system, one of which is the introduction of community service as an alternative to short-term imprisonment. This community service activity aims to provide an understanding to students of SMK Muhammadiyah 02 South Tangerang City regarding the substance of the new KUHP, particularly related to community service penalties, as well as to analyze the readiness of law enforcement officials in implementing it. The method used is interactive socialization through lectures, discussions, and case simulations. The results of the activity indicate that participants’ understanding of community service penalties increased significantly, from 35% to 82% based on pre-test and post-test evaluations. On the other hand, the analysis of law enforcement readiness shows that although the regulatory framework is already in place, there are still challenges such as limited infrastructure, the need for cross-sectoral coordination, and the transformation of legal culture in society. This article concludes that the successful implementation of community service penalties requires synergy between regulatory readiness, institutional capacity, and social acceptance.